Landslide and debris flow hazards in the Mugling-Narayangarh Highway section, central Nepal - Adhikari, DP; Joshi, SR (Journal of Nepal Geological Society, 2008)
The Mugling–Narayangarh (MUNA) Highway section belongs to the Siwaliks in the south and the Lesser Himalaya in the north. The Siwaliks consist of boulder beds, conglomerates and sandstones whereas the Lesser Himalayan rocks include the Kunchha Formation, Fagfog Quartzite, Dandagaun Phyllites, Nourpul Fommation, Dhading Dolomite, and Benighat Slates. The Main Boundary Thrust (MBT) and three other thrusts, namely the Kamalpur Thrust (KT), Simaltal Thrust (ST), and Virkuna Thrust (VT) in the north of the MBT and a large number of normal faults and folds of local and regional scales are the main tectonic features in the area. Brittle rocks, especially dolomite, quartzite, and amphibolite are jointed and intensely fractured, making the slope vulnerable to rock falls and slides. Phyllites and slates have undergone high degree of weathering and have some ductile deformations. The basin has either unstable dip slopes mantled by discontinuous, thick unconsolidated soil cover or vertical cliffs. Bouldery loose sagging masses are widespread and the slopes are chronically unstable at places. Sometimes the whole mountain appears moving down under the influence of toe cutting action. Landslide and landslide-induced debris flow, especially during the monsoon period, are the common causes of damage, destruction and casualties and frequent Highway blockage in the MUNA section. Concept of three stability states - stable, marginally stable, and actively unstable states, offers a useful framework for understanding the causes and development of slope instability. It can be viewed as existing at various points along a stability spectrum ranging from high margins of stability with low probabilities of failure at one end, to actively falling slopes, with no margin of stability, at the other. Four groups of factors, such as pre-disposing, preparatory, triggering and sustaining factors were identified in promoting the instabilities. The preparatory destabilizing factors effective in long-term include weathering, tectonic uplift, thrusting, faulting, and shearing, and that effective in short-term are erosion, deforestation, and other human activities. Intense or sustained rain fall of monsoon season or their combination, seismic shaking, and slope undercutting are the key triggering factors. Rainfall, progressive state of landslide movement, the presence of terrain in the landslide path and other inherent material properties are the sustaining destabilizing factors. For the purpose of landslide hazard assessment, the MUNA areas was divided into rock and soil slopes and the ratings for geological, engineering geological, geomorphic and other attributes were applied and a landslide hazard map was prepared. Based on the hazard rating, the area was divided into low, medium, high, and very high hazard zones. The low hazard zone is considered stable, whereas the medium hazard zone may have possibilities of landslide occurrence for the given conditions. Old landslides with some renewed activities and some areas without actually initiating movement but having marginal stability due to active geological process and increased human activities are placed under the high hazard zone. Areas in and adjacent to the fault and thrust zones with active landslides and the terrain encountered in the landslide path are considered as very high hazard zones. The low, medium, high and very high hazard zones delineated in the area are estimated to represent about 30 %, 40 %, 15%, and 15 % of the total area, respectively. The geological and tectonic processes and engineering geological conditions are the main factors in the occurrence of landslide and debris flows while rainfall and other human activities are the main triggers. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.26